2019
DOI: 10.1007/s40831-019-00237-7
|View full text |Cite
|
Sign up to set email alerts
|

Slag Cleaning Equilibria in Iron Silicate Slag–Copper Systems

Abstract: In this study, the equilibrium distributions of selected trace elements between molten iron-saturated copper alloy and selected iron silicate slags were measured, and the effects of silica fluxing on them. In addition to the copper and iron main components of the system, trace elements like antimony, gallium, germanium, gold, indium, and silver were added in experiments that spanned the temperature range of 1473-1573 K (1200-1300 °C). Experimental charges were quenched and prepared in polished mounts. In situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…It was observed that the increasing silica concentration in the slag has an increasing effect on cobalt distribution coefficient. This information is in agreement with the study of Hellstén et al [37] on slag cleaning equilibria in iron silicate slag-copper system. According to their observations, Fe/SiO 2 ratio has a significant effect on trace elements distribution between metal alloy and the slag.…”
Section: Distribution Of Cobalt Between Metal Alloy and The Slagsupporting
confidence: 92%
See 3 more Smart Citations
“…It was observed that the increasing silica concentration in the slag has an increasing effect on cobalt distribution coefficient. This information is in agreement with the study of Hellstén et al [37] on slag cleaning equilibria in iron silicate slag-copper system. According to their observations, Fe/SiO 2 ratio has a significant effect on trace elements distribution between metal alloy and the slag.…”
Section: Distribution Of Cobalt Between Metal Alloy and The Slagsupporting
confidence: 92%
“…According to their observations, Fe/SiO2 ratio has a significant effect on trace elements distribution between metal alloy and the slag. Hellstén et al concluded that reduction of metal oxides can be optimized by adjusting SiO2 concentration in slag and the goal should be to maintain the slag compositions higher than about 28 wt% [37]. The previous study of Ruismäki et al together with the present study confirmed these findings, even though the silica concentration in the slag in this study was much higher, 35-43 wt% [24] versus 51-59 wt%, respectively.…”
Section: Distribution Of Cobalt Between Metal Alloy and The Slagsupporting
confidence: 80%
See 2 more Smart Citations
“…However, in comparison to previous investigations, the concentrate used in our study contained much more zinc. The Fe/SiO 2 flux ratio was approximately 1.88, which corresponds to the orthosilicate composition, shown to be effective for minimizing the trace element losses into the slag [32]. The amounts of La and Nd oxides added to the mixture were both 5% of the mass of the concentrate.…”
Section: Raw Materials and Sample Preparationmentioning
confidence: 99%